High‐Performance Photodiode Based on Atomically Thin WSe2/MoS2 Nanoscroll Integration. Issue 30 (23rd May 2019) - Deng, Wenjie; You, Congya; Chen, Xiaoqing; Wang, Yi; Li, Yufo; Feng, Beibei; Shi, Ke; Chen, Yongfeng; Sun, Ling; Zhang, Yongzhe
Abstract: Self‐assembled structures of 2D materials with novel physical and chemical properties, such as the good electrical and optoelectrical performance in nanoscrolls, have attracted a lot of attention. However, high photoresponse speed as well as high responsivity cannot be achieved simultaneously in the nanoscrolls. Here, a photodiode consisting of single MoS2 nanoscrolls and a p‐type WSe2 is demonstrated and shows excellent photovoltaic characteristics with a large open‐circuit voltage of 0.18 V and high current intensity. Benefiting from the heterostructure, the dark current is suppressed resulting in an increased ratio of photocurrent to dark current (two orders of magnitude higher than the single MoS2 nanoscroll device). Furthermore, it yields high responsivity of 0.3 A W −1 (corresponding high external quantum efficiency of ≈75%) and fast response time of 5 ms, simultaneously. The response speed is increased by three orders of magnitude over the single MoS2 nanoscroll device. In addition, broadband photoresponse up to near‐infrared could be achieved. This atomically thin WSe2 /MoS2 nanoscroll integration not only overcomes the disadvantage of MoS2 nanoscrolls, but also demonstrates a single nanoscroll‐based heterostructure with high performance, promising its potential in the future optoelectronic applications. Abstract : A MoS2 nanoscroll‐based heterostructure integrated with atomically thin WSe2 is constructed, which exhibits well‐rounded performance with a high external quantum efficiency of 75%, open‐circuit voltage of 0.18 V and a fast response speed of 5 ms. It not only makes up for the inferiority of single MoS2 nanoscroll photodetectors, but also demonstrates the potential of nanoscrolls in nano‐optoelectronics.